Proprioceptive Neuromuscular Facilitation Protocol for Thumb Osteoarthritis: A Pilot Study - Cantero-Téllez, Raquel; Naughton, Nancy; Algar, Lori A.; Medina-Porqueres, Iván; Cruz Gambero, Leire; Valdes, Kristin (Sage Journals, 2023)
Background: Osteoarthritis (OA) of the thumb carpometacarpal (CMC) joint often presents with joint instability and proprioceptive deficits. Proprioception has been found to play an important role in the rehabilitative process. The purpose of this study was to evaluate the effectiveness of a proprioceptive training program on pain and function in individuals with early-stage thumb Carpometacarpal joint OA. Methods: A double-blind experimental trial using a 2-group pretest/posttest design was used in this pilot study. Participants had a diagnosis of grade I and II thumb CMC joint OA in their dominant hand and a pain rating of >4/10 on Visual Analogue Scale. Participants received either standard treatment (control group) or standard treatment plus a proprioceptive training program (experimental group). Outcome measures were lateral pinch strength, pain intensity during activities, and proprioceptive response via joint position sense (JPS) testing. Results: Twelve individuals (average age of 66.25 years) participated. Both groups had a statistically significant decrease in pain and increase in lateral pinch strength, all occurring with a large effect size but no statistically significant difference between groups. The experimental group experienced a large effect size for JPS testing, whereas the control group experienced a trivial effect size, and there was a statistically significant difference between groups for JPS testing. Conclusions: Individuals who completed the proprioceptive training program in this study had an improvement in proprioceptive functioning. This program shows potential for routine inclusion in hand therapy for thumb CMC joint OA; however, additional high-level studies with larger sample sizes are required.
Keywords: Manos - Lesiones y heridas; Artritis; anatomy; arthritis; basic science; cartilage; diagnosis; osteoarthritis; proprioception; rehabilitation; specialty; thumb